El engagement y desempeño laboral en la escuela técnico superior polícia nacional del Perú Iquitos abril 2024 - Moya Vásquez, Kelly Elizabeth (2025)
Engagement in any type of company, of any economic branch, is very important because it facilitates work performance and goals are easily met, because there is high motivation in them and they are happy with the work they do. This thesis seeks to determine the relationship between Engagement and job performance in the administrative and teaching collaborators of the National Police Higher Technical School of Peru Iquitos April 2024, the research is applied with a quantitative approach, correlational level, non experimental and cross-sectional design The work concludes that there is a moderate and significant positive relationship between Engagement and job performance with a Pearson coefficient of 0.526 and a significance value of 0.001, less than 0.05, it also determined that the respondents' perception of The variable engagement and work performance is high.